Partisipasi Masyarakat dalam Pengembangan Destinasi Wisata di Pantai Natsepa Kecamatan Salahutu Kabupaten Maluku Tengah - Molle, Lucas P. (Agrikan: Jurnal Agribisnis Perikanan, 2020)
This study aims to describe the forms and levels of participation at the planning, implementation, enjoying the results and evaluation of tourism development programs, by describing the process of forming participation and the process of transitioning participation forms from individual level (tourism entrepreneurs) to communities (Tourism Aware Groups), from the level individuals become organizations (Village-Owned Enterprises), as well as from the community level into tourism organizations and the process of organizing individuals, groups and organizations to reach the stage of public power (citizen power) in each stage of development (planning, implementation, enjoying the results and evaluation) at the destination tour of Natsepa Suli Beach, Central Mollucas Regency. This research will use qualitative research methods, to describe community participation in planning, implementing, enjoying the results and evaluating tourism development programs. Data collection techniques in this study used in-depth interviews (in-depth interviews), observation and document study. In addition, the Researcher organized a Focus Group Discussion (FGD) to discuss matters related to tourism development issues as well as related to factors supporting and inhibiting participation. Thus, it is expected that with the participation of the community in the tourism planning process, it can provide an opportunity for the community to express ideas and expectations related to tourism development so that the tourism development program implemented is able to answer the needs of the local community, and it is hoped that the results of this study can be accepted published in the National Journal.